Do Transparent Moneyboxes increase Savings? A Note on Visual Feedback and Savings Behavior - Albrecht Bohne; Avdeenko Alexandra; Markus Frölich; Niels Kemper (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Limited attention may play a role in explaining the inability to reach savings goals (Karlan, McConnell, Mullainathan and Zinman, forthcoming). Presuming that attention is a scarce resource and important for the pursuit of saving plans, limits to attention in inter-temporal consumption and saving decisions may cause savers not to reach their savings goals. In turn, constant feedback on the savings performance may help to reach savings goals in the presence of limited attention. In this presentation we will draw on a simple experiment to test whether the visual representation of savings balances stimulates savings behavior and helps individuals reach their savings goals. Doing so, we randomly offer transparent and non-transparent moneyboxes as a complementary savings device to current and former clients of a microfinance organization in Ethiopia. We test whether the visual representation of saving balances via transparent money boxes increases savings and helps microfinance clients reach their savings goals. While this is our working hypothesis, we also test whether the visual representation of saving balances via transparent money boxes decreases savings (i.e. because of a higher temptation to spend money that can be seen, or because it is more difficult to hide savings from others). The hypotheses are currently under investigation as the final phase of the data-collection was completed in February 2015.
Keywords: D12; D91; O12; 330